2019
DOI: 10.1080/23322039.2019.1630161
|View full text |Cite
|
Sign up to set email alerts
|

Macro-determinants of short-term foreign debt in Ghana

Abstract: This study tests the validity of the hypothesis that the regulatory and macroeconomic environments and the disparity between domestic and international interest rates are important determinants of short-term foreign debt stock in a developing economy like Ghana. This study employs a time series econometric analysis of annual secondary data covering the period 1970 to 2012. More specifically, the bounds testing approach is used to estimate the impact of potential determinants-identified in the theoretical and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…Raising external debt as a significant means to finance fast economic development and importing innovations into the BRICS countries renders their financial markets more susceptible to exogenous pressures and shocks, leading to an irrational strengthening of national currencies. Brafu-Insaidoo, Ahiakpor, Vera Ogeh, & William (2019) found that a decrease in regulatory constraints on foreign borrowing, and between international and domestic interest rates, the performance of GDP and the deepening of financial resources lead, in both the long and short runs, to an increase in the short-run external debt. Kregel (2020) examined the link between foreign debt and monetary sovereignty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Raising external debt as a significant means to finance fast economic development and importing innovations into the BRICS countries renders their financial markets more susceptible to exogenous pressures and shocks, leading to an irrational strengthening of national currencies. Brafu-Insaidoo, Ahiakpor, Vera Ogeh, & William (2019) found that a decrease in regulatory constraints on foreign borrowing, and between international and domestic interest rates, the performance of GDP and the deepening of financial resources lead, in both the long and short runs, to an increase in the short-run external debt. Kregel (2020) examined the link between foreign debt and monetary sovereignty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With a few exceptions, most studies based on panel and cross-sectional data did not use the dynamic estimation techniques like panel ARDL. Similarly, only a few studies used ARDL in single-country cases (such as Abdullahi et al 2015;Adamu -Rasiah 2016;Adane et al 2018;and Brafu-Insaidoo et al 2019). Table 1 also shows that among HIPCs, only Ghana, Ethiopia, and Uganda have been studied.…”
Section: Theoretical Framework and Empirical Literaturementioning
confidence: 99%
“…Common determinants of external debt reported in existing literature are economic growth, imports, population, foreign exchange reserves, total debt service, poverty, income instability, depreciation of the currency, budget deficit, exchange rate, trade openness, terms of trade, inflation, interest rate, national savings, and financial development (Abdullahi, Bakar, and Hassan 2015;Bittencourt 2015;Lau, Lee, and Apir 2015;Vighneswara 2015;Lau and Lee 2016;Al-Fawwaz 2016;Belguith and Omrane 2017;Özata 2017;Udoh and Rafik 2017;Chiminya, Dunne, and Nikolaidou 2018;Chirwa and Odhiambo 2018;Adamu 2019;Brafu-Insaidoo et al 2019;Fatukasi et al 2020). For instance, Vighneswara (2015) and Beyene and Kotosz (2020a) asserted that government expenditure is one of the key factors that increase external debt due to budget deficits, which compel governments to borrow.…”
Section: Introductionmentioning
confidence: 99%